Intellectualism and the argument from cognitive science. (4th July 2019) - Schwartz, Arieh; Drayson, Zoe
ABSTRACT: Intellectualism is the claim that practical knowledge or 'know-how' is a kind of propositional knowledge. The debate over intellectualism has appealed to two different kinds of evidence, semantic and scientific. This paper concerns the relationship between intellectualist arguments based on truth-conditional semantics of practical knowledge ascriptions and anti-intellectualist arguments based on cognitive science and propositional representation. The first half of the paper argues that the anti-intellectualist argument from cognitive science rests on a naturalistic approach to metaphysics: Its proponents assume that findings from cognitive science provide evidence about the nature of mental states. We demonstrate that this fact has been overlooked in the ensuing debate, resulting in inconsistency and confusion. Defenders of the semantic approach to intellectualism engage with the argument from cognitive science in a way that implicitly endorses this naturalistic metaphysics, and they even rely on it to claim that cognitive science supports intellectualism. In the course of their arguments, however, they also reject that scientific findings can have metaphysical import. We argue that this situation is preventing productive debate about intellectualism, which would benefit from both sides being more transparent about their metaphilosophical assumptions.